Varus kinematics at knee flexion affect clinical outcomes of unicompartmental knee arthroplasty: Intraoperative navigation-based kinematics evaluation - Kousuke Shiwaku; Atsushi Teramoto; Satoshi Nuka; Takashi Matsumura; Kota Watanabe; Toshihiko Yamashita (Elsevier, 2020)
Background: The aim of the study was to investigate the effects of navigation-based varus or axial rotational alignment through knee flexion on patient reported outcomes or the maximum flexion angle of unicompartmental knee arthroplasty (UKA). Methods: Data were retrospectively collected from 46 knees that underwent UKA for medial unicompartmental knee osteoarthritis. An image-free knee navigation system was used in all cases, and intraoperative varus and axial rotational alignment at every knee flexion angle were recorded before and after implantation. All patients completed the Knee injury and Osteoarthritis Outcome Score (KOOS) at final follow-up. By varus or valgus at 0° knee flexion, the knees were subdivided into two groups (varus at 0° group, varus above the median value; neutral at 0° group, varus equal to or below the median value). By varus or valgus at 90° knee flexion, patients were similarly subdivided into two groups (varus at 90° group; neutral at 90° group). The maximum knee flexion angle was measured 3 months after surgery. Results: There were no differences in the KOOS between the neutral at 0° group and the varus at 0° group. However, the KOOS activity score (79 ± 17 vs 69 ± 16, p = 0.02) and the KOOS total score (72 ± 17 vs 65 ± 15, p = 0.03) of the neutral at 90° group were better than those of the varus at 90° group. The alignment and the maximum knee flexion angle 3 months after surgery were not correlated. Conclusion: Varus at 0° knee flexion and axial rotational alignment did not affect the clinical outcomes of UKA. Patient reported outcomes was better for the neutral knees with less varus at 90° knee flexion than for varus knees. Keywords: Unicompartmental knee arthroplasty, Navigation, Kinematics, Alignment, Varus